Transporter-centric view of urate metabolism: From genome-wide association study to pathophysiology - Hiroyuki Sakurai (Japanese Society of Physical Fitness and Sports Medicine, 2012)
While urate is an important anti-oxidant molecule in the body, high plasma levels of urate cause morbidity including urate crystal deposition in joints (gout) and stone formation in the urinary tract. Because urate is an end product of purine metabolism, it must be excreted from the body via the kidneys or intestinal tract. Despite its low water solubility, this negatively charged molecule cannot permeate the cell membrane without specific proteins called transporters. In the kidney proximal tubule, the relatively urate-specific transporters, URAT1 and URATv1, serve as a urate reabsorptive path, while the broad specific transporters, OAT1/3 and NPT1/4, are utilized for urate secretion. For sports medicine audiences, renal hypouricemia and exercise-induced acute renal failure resulting from URAT1 or URATv1 mutation may be of interest. URATv1 seems to play a role in urate transport into blood from the liver, a major organ for urate production, and ABCG2 is critical for urate excretion into the intestine. Many of these transporters have been identified by genome-wide association studies (GWASs) linking high plasma urate levels and/or gout to single nucleotide polymorphisms (SNPs) in these transporter genes. While GWASs are a very powerful approach in searching for genes associated with disease, cell biological and physiological characterization of candidate gene products is critical for elucidation of (patho) physiology.